Flavonoids in the treatment of Leishmania amazonensis: a review of efficacy and mechanisms - Lessa, Vinicius Lopes; Drescher, Guilherme; Gonçalves, Gustavo; Lopes, João Carlos Baptista; Vieira, Rafael Felipe da Costa; Figueiredo, Fabiano Borges (Frontiers in Pharmacology, 2025)
Leishmaniasis is caused by protozoan parasites of the genus Leishmania. In recent years, natural compounds have attracted significant interest due to their potential efficacy and lower toxicity compared to synthetic chemical compounds. This review analyzed studies retrieved from the PubMed and Google Scholar databases, focusing on the use of flavonoids against Leishmania amazonensis. Only studies testing flavonoids with known activity against the parasite were included and categorized according to their leishmanicidal efficacy. Based on the criteria established to identify the most comprehensive studies, 52 were included in the analysis. Of these, three studies met at least 13 of the evaluation parameters (70%) and were considered the most complete. Analysis of IC50 values reported in these articles revealed the activity of 69 flavonoids. Among the assays on amastigote forms, 33 reported high activity, and six reported moderate activity. For assays on promastigote forms, 32 experiments reported high activity, 16 showed moderate activity, and two demonstrated weak activity. Of the flavonoids tested, morelloflavone-4‴O-β-D-glycosyl and pinostrobin showed the highest activity, while naringenin exhibited the weakest activity, specifically against promastigote forms. In the cytotoxicity assays, carajurin and luteolin exhibited the highest selectivity indices reported in the articles. This review emphasizes the importance of studying flavonoids, particularly those extracted from plants and propolis, to advance our understanding and treatment of L. amazonensis infections.